Large-scale OMNeT++-based deterministic networking simulation practice - Chenqiang GAO; Xiangyang ZHU; Jinghai YU (Dianxin kexue)
TSN and DetNet are major components of the deterministic networking solution, detailed research has been conducted by industry and academia.However, the study seldom considers the joint of these two technologies under large-scale networks.To facilitate the analysis of the joint networks, TSN and DetNet specifific extensions to the popular OMNeT++/INET framework for network simulations was presented, in particular, the time slot scheduling, the TSN node/host/interface and DetNet node/host/interface, the framework for collaboration between the controller and the simulation system.A proof of concept implementation and exemplary evaluation of the joint of these two technologies under large-scale networks was presented.The results show that in large-scale cross-domain scenarios, the time slot scheduling mechanism can provide end-to-end deterministic service guarantee.